Introduction: positions of Asian donors in the aid discourse toward post-2015. Issue 1 (20th December 2013) - Yamada, Shoko
Abstract : Purpose: – This purpose of this paper is to provide the context in which this special issue is published. This special issue highlights the matters related to the Asian countries which provide assistance to developing countries for their advancement of education. There are an increasing number of donor countries which are formerly recipients of development assistance. Their emergence as donors is changing the landscape of international educational development. Being outside of the self-regulating community of traditional donors, they bring different logics and motivations to this field that often go beyond the frame of meaning making among traditional donors. Asia-Pacific region is unique in the sense that it has both traditional and new types of donors. The former group includes Japan and the USA, while the latter has Korea, China, India, and many others. Design/methodology/approach: – As the introduction to the collection of articles which introduce characteristics of diverse donors (traditional and nontraditional) in the Asia-Pacific region, this paper discusses first, changing the normative framework toward the target year of achieving Education for All goals, which is 2015; second, the background for the nontraditional donors to increase their presence and the changed landscape of international educational development; and third, commonalities and differences among Asian donors in terms of their philosophies, structures, and histories. Findings: – This paper maps out the locations of each Asian donors discussed in the respective country cases to follow and highlights some Asian characteristics. Originality/value: – The findings would hint at the presence of principles and logics of educational cooperation which cannot be fully grasped by applying widely diffused western notions of educational development.